2008
DOI: 10.1002/iroh.200711046
|View full text |Cite
|
Sign up to set email alerts
|

Food Web Paradigms: The Biochemical View on Trophic Interactions

Abstract: Different metabolic pathways and requirements can lead to imbalances in the biochemical composition, e.g., between prokaryotes and eukaryotes and between heterotrophic and autotrophic organisms. In addition, heterotrophs cannot synthesize many of the required biochemical constituents themselves but rely in their provision on the feeding environment. If imbalances of essential biochemicals between heterotrophic consumers and their prey are large, those biochemicals can become limiting. The importance of essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
100
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(103 citation statements)
references
References 154 publications
1
100
1
1
Order By: Relevance
“…Strong correlative evidence and supplementation experiments strongly suggest that the content of polyunsaturated fatty acids (PUFAs) in phytoplankton determines the trophic transfer efficiency in freshwater food webs (Müller-Navarra, 2008). Within aquatic foodwebs, both, n-3 and n-6 PUFAs are provided almost exclusively by primary producers (i.e., phytoplankton, macrophytes).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong correlative evidence and supplementation experiments strongly suggest that the content of polyunsaturated fatty acids (PUFAs) in phytoplankton determines the trophic transfer efficiency in freshwater food webs (Müller-Navarra, 2008). Within aquatic foodwebs, both, n-3 and n-6 PUFAs are provided almost exclusively by primary producers (i.e., phytoplankton, macrophytes).…”
Section: Discussionmentioning
confidence: 99%
“…In case of the interaction of phytoplankton with Daphnia, this reasoning leads to the question, how effects of temperature on Daphnia somatic growth due to increased phytoplankton abundance in warmer environments can be disentangled from effects of changes in PUFA concentration per unit phytoplankton mass. However, in correlative studies, in which Daphnia growth on natural phytoplankton was related to the abundance of edible phytoplankton (measured as particulate organic carbon, POC) and the prevalence of EPA in natural phytoplankton, food abundance explained considerably less of the variance in Daphnia growth than the EPA-content: r 2 POC = 0.62, r 2 EPA = 0.93 (Müller-Navarra, 1995); r 2 POC = 0.55, r 2 EPA = 0.95 (Müller-Navarra et al, 2000); r 2 POC = 0.60; r 2 EPA = 0.77 (Wacker and Von Elert, 2001), which suggests that Daphnia growth in nature is not limited by food quantity but rather by food quality except for nutrient-poor lakes (Persson et al, 2007;Müller-Navarra, 2008). The correlative finding that Daphnia abundance is most frequently not constrained by food quantity is mainly due to the fact that in lakes and ponds Daphnia serves as major food item for planktivorous fish and invertebrate predators, so that during most of the season Daphnia abundances do not reach carrying capacity (Sommer et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Together with nutrient accessibility, irradiance has been identified as the most important environmental factor steering ice algal growth (Cota et al 1991). Moreover, these factors largely determine algal nutritional quality in terms of fatty acid composition (Thompson et al 1990, Reitan et al 1994) and elemental stoichiometry (Sterner & Elser 2002) with corresponding implications for higher trophic levels (Muller-Navarra 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the ω6-HUFA ARA was found to be a major HUFA component of polyps, which may have implications for the jellyfish life history and food web processes. Unlike the ω3-HUFA EPA and DHA, for which beneficial effects to resist environmental stress in fish (Sargent et al, 1999), enhance growth and reproduction in zooplankton (Sundbom and Vrede, 1997;Abrusán et al, 2007;Müller-Navarra, 2008), the functional importance of ARA in aquatic food webs is less documented with exceptions of few studies from fishery (Yuan et al, 2015). ARA concentration in fish tissue seems to be diet dependent, and functionally regulating fish larval growth, survival, immune function and resistance to stress (reviewed by Bell and Sargent, 2003).…”
Section: Fa Composition Of Polyps Affected By Dietary Famentioning
confidence: 99%